STUDY OF THE EFFECTIVENESS OF IMPOSITION OF LYMPHATIC-VENOUS ANASTOMOSIS FOR THE PREVENTION OF SECONDARY LYMPHEDEMA AFTER RADICAL TREATMENT PATIENTS WITH BREAST CANCER (PRELIMINARY RESULTS) - Uzakov Sohib Makhsudovich, Juraev Mirjalol Dehkanovich , Karimova Mavluda Nematovna (Journal Park Publishing, 2023)
Prevention of secondary lymphedema (LL) after radical treatment of breast cancer (BC) is an urgent task of modern oncology. Description of preliminary results of a study of the effect of radical mastectomy (RME) with lymphatic-venous anastomosis (LVA) on the frequency of VL, 5-year survival of patients and the risk of VL, conducted in the Samarkand region . And out of 1078 registered for the first time in 2017-2020. patients with breast cancer, subjected to RME according to clinical indications, made up a sample of 190 patients, dividing it into three groups. Group I consisted of 70 patients with I - IIIA stages of breast cancer, subjected to RME according to Madden with simultaneous application of LVA; group II - 120 patients randomly selected from the remaining 1008 patients subjected to RME without LVA. Subgroup II and group II included 92 patients with stage I - IIIA breast cancer ( 76.67%) ; in subgroup II b - the remaining 28 with stages IIIB , IIIC and IV , metachronous breast cancer ( 23.33% ) . During the study period, 22 patients died (11.58%): in group II - 15 (12.50%), 11 of them - in subgroup IIa (11.96%), 4 - in II b (14.29% ) ;, differences are not significant ( p >0.05). The mean follow-up period in the sample was 28.5 months: in group II - 26.9, in subgroup IIa - 28.3, in subgroup IIb - 22.18; in group I - 30.0. The distribution of patients in groups I and II by stages was statistically similar ( p >0.05 ). RME with LVA had no effect ( p >0.05) on the dynamics of the five-year survival of patients compared with conventional RME. RME with LVA reduced the risk of VL ( p < 0.05) in patients with breast cancer for 5 years, which did not depend on the stage of breast cancer. The results indicate the high efficiency of LVA in patients of the II clinical group, falling under the indications for the use of RME .